The Afrikaans Bible translations and apartheid - J. A. Naudé (Acta Theologica)
A comparison of quotes from the document on race relations viewed in the light of the scriptures to the Hebrew and Greek source text bears eloquent testimony to the fact that the nature of the first Afrikaans translation and its revision as a source text oriented translation encouraged the justification of apartheid. In this translation the strategy of intensification/explication of the source texts items is applied in most cases. The result is that apartheid vocabulary is highlighted. The second translation of the Afrikaans Bible goes pari passu with acquiescent social consciousness among the Afrikaners. This translation as a target text oriented translation introduces a new vocabulary of reconciliation, clearly apparent from the quotes contained in the document on church and society. The strategies of substitution, generalisation, deletion and paraphrase are applied. The apartheid vocabulary is downplayed. The reconciliation vocabulary gave moral support for the Afrikaner to give consent for a new dispensation.